1982
DOI: 10.1116/1.571329
|View full text |Cite
|
Sign up to set email alerts
|

Summary Abstract: Improved adhesion of Ni films on x‐ray damaged polytetrafluoroethylene

Abstract: Chemically deposited Ni on Si(111) investigated with xray standing waves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
9
2
Order By: Relevance
“…Metalization of PTFE has been studied extensively due to its importance in microelectronic device fabrication and packing technologies. Previous metalization studies have been carried out on PTFE using Na, Ag, Cu, , Cr, , Ti, , Al, , Ni, , and Au. ,, In general, results from these studies have revealed that metalization is accompanied by defluorination of the polymeric interface and formation of a metal fluoride layer. At higher exposures a metallic overlayer is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Metalization of PTFE has been studied extensively due to its importance in microelectronic device fabrication and packing technologies. Previous metalization studies have been carried out on PTFE using Na, Ag, Cu, , Cr, , Ti, , Al, , Ni, , and Au. ,, In general, results from these studies have revealed that metalization is accompanied by defluorination of the polymeric interface and formation of a metal fluoride layer. At higher exposures a metallic overlayer is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of polymer surfaces prior to metal deposition has been shown to enhance metal adhesion [6][7][8][9][10][11][12]. Along with wet chemical treatment, ion bombardment *To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that chemical bonding at the interface is important to metal/polymer adhesion in general, , and metal/polyimide adhesion in particular, where metals have been deposited by evaporation or sputtering. A similar conclusion has been reached for metal/fluoropolymer systems, although it is unclear what reaction is responsible for adhesion . For the less reactive fluoropolymers, it is usually necessary to modifiy the surface to enhance that interaction.…”
Section: Introductionmentioning
confidence: 52%